2009
DOI: 10.4049/jimmunol.0803845
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and NK/CD4+ T Cell-Dependent Efficient Prevention of Lung Metastasis Induced by Dendritic Cells Harboring Recombinant Sendai Virus

Abstract: We recently demonstrated efficient antitumor immunity against murine tumors using dendritic cells (DCs) activated by recombinant Sendai viruses (rSeVs), and proposed a new concept, “immunostimulatory virotherapy,” for cancer immunotherapy. However, there has been little information on the efficacy of this method in preventing metastatic diseases. In this study, we investigated the efficacy of vaccinating DCs activated by fusion gene-deleted nontransmissible rSeV (rSeV/dF) using a murine model of lung metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…The effect of SeV on immune modulation is further highlighted in a study by Komary et al, which showed that SeV-transduced dendritic cells can induce persistent NK and CD4-cell-dependent anti-tumor activity. 20 We have previously shown that SeV administration evokes cellular and humoral immune responses in an animal model and that the level of neutralising antibodies (as measured by in vitro assays) increases after virus re-administration. 7 However, there was no correlation between neutralising antibody levels and residual gene expression (r 2 ¼0.046, P¼0.16).…”
Section: Discussionmentioning
confidence: 97%
“…The effect of SeV on immune modulation is further highlighted in a study by Komary et al, which showed that SeV-transduced dendritic cells can induce persistent NK and CD4-cell-dependent anti-tumor activity. 20 We have previously shown that SeV administration evokes cellular and humoral immune responses in an animal model and that the level of neutralising antibodies (as measured by in vitro assays) increases after virus re-administration. 7 However, there was no correlation between neutralising antibody levels and residual gene expression (r 2 ¼0.046, P¼0.16).…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, rSeVs lead DCs to highly activated/mature state via a DExD/Hbox RNA helicase, retinoic acid-inducible gene-I (RIG-I; refs. 13,14); therefore, we have been able to show that DCs activated by rSeVs (DC-rSeV) induced highly efficient antitumor immunity against various tumors (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Construction and recovery of rSeVs rSeVs were constructed as described previously (7)(8)(9). In brief, LLC-MK2 cells were transfected with a plasmid mixture containing each of the following plasmids: pSeV þ 18/dF-GFP (green fluorescent protein) or pSeV þ 18/dF-hsFLT-1 (16), pGEM-NP, pGEM-P, and pGEM-L in Superfect reagent (Qiagen).…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
See 2 more Smart Citations